Archetypical semantics of ornithonyms in the artistic idiolect of O. Dovzhenko - Дорошина, Лілія Федорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article dealts with the archetype as poliaspect lingvomental phenomenon and analyzes the origins and development of this concept. The article also examines ethno-cultural archetypal images bird names (ornithonyms) as define elements of the Ukrainian space that form the language of the writer’s works megaimage of the country, its national mentality. It has been analysed of verbal methods which represent these images of Dovzhenko’s literary works. The actual study material is a language of screenplays such as «Earth», «The Charmed Desna», «The Novel of Fiery Years», and a story «Mother».